Deforestation for agriculture increases microbial carbon use efficiency in subarctic soils - Schroeder, Julia; Peplau, Tino; Pennekamp, Frank; Gregorich, Edward; Tebbe, Christoph C.; Poeplau, Christopher (Zenodo, 2022)
This repository contains all necessary raw data as well as the R code used to conduct statistical analysis and create figures of the publication Deforestation for agriculture increases microbial carbon use efficiency in subarctic soils Julia Schroeder1, Tino Peplau1, Frank Pennekamp2, Edward Gregorich3, Christoph C. Tebbe4, Christopher Poeplau1 1 Thünen Institute of Climate-Smart Agriculture, Bundesallee 68, 38116 Braunschweig, Germany 2 Department of Evolutionary Biology and Environmental Studies, University of Zurich, Winterthurerstrasse 190, 8057 Zürich, Switzerland 3 Research and Development Centre, Central Experimental Farm, Agriculture and Agri-Food Canada, 960 Carling Ave, Ottawa, Ontario K1A 0C6, Canada 4 Thünen Institute of Biodiversity, Bundesallee 65, 38116 Braunschweig, Germany DOI: https://doi.org/10.1007/s00374-022-01669-2 This study investigated how and through which pathways deforestation and conversion to agricultural land (i.e. grassland, cropland) alters the microbial carbon use efficiency (CUE) in subarctic soils to allow the development of mitigation strategies to alleviate C losses. We assessed CUE using 18O-labelled water in a paired-plot approach on soils collected from 19 farms across the subarctic region of Yukon, Canada, comprising 14 pairs of forest-to-grassland conversion and 15 pairs of forest-to-cropland conversion. Microbial CUE significantly increased following conversion to grassland and cropland. Land-use conversion resulted in a lower estimated abundance of fungi, while the archaeal abundance increased, as assessed by qPCR. Interestingly, structural equation modelling revealed that increases in CUE were mediated by a rise in soil pH and a decrease in soil C:N ratio rather than by shifts in microbial community composition, i.e. the ratio of fungi, bacteria and archaea. Our findings indicate a direct control of abiotic factors on microbial CUE via improved nutrient availability and facilitated conditions for microbial growth. The R code was developed under R v3.6.3 and adapted ...